Metabolomics: A novel approach in pharmacognosy researches - Khatib, Alfi (2020)
Pharmacognosy is entering a new phase employing big data related to system biology. This approach requires a new holistic tools called metabolomics. In this presentation the application of metabolomics in pharmacognosy is discussed including: 1. Analysis of known bio-active compounds and screening of metabolites in the extracts prior to isolation of unknown bio-active compounds, 2. Analytical tool in quality control and process optimization of herbal products based on the fingerprint of their metabolites, and 3. Comprehensive bio-activity and toxicity evaluation of the herbal products